MAMA MODEL APPROACH: ITS IMPLICATION TO COMMITMENT AND ORGANIZATIONAL CITEZENSHIP BEHAVIOR OF OPERATIONAL HOTEL EMPLOYEE - Udiyana, Ida Bagus Gede; Wignjohartoyo, Parwoto; Sulasmi, Siti (Jurnal Dinamika Manajemen, 2015)
The aims of this study is to find the existence of MAMA (Motivation, Ability, and Moral Awareness) model to the commitment and Organizational Citizenship Behavior (OCB). The subject of the research is the five stars hotels at Nusa Dua Bali. Respondents of this study are the operational employees at the hotels who have Hindu religion with 198 samples. The method of collecting data was simple random sampling method with proportional allocation. Structural Equation Modeling (SEM) analysis technique was utilized to analyze the data in this research. This research has found that MAMA model (Motivation, Ability, and Moral Awareness) influences OCB. Furthermore this research has found a theory that the main variable which is causing the appearance of organizational citizenship behavior is MAMA (motivation, ability, and moral awareness) as an intrinsic behavior, and commitment or organizational citizenship behavior function of MAMA, and commitment or to be formulated as OCB f. Info